The World's Water Volume 8 The Biennial Report on Freshwater Resources - Gleick, Peter H.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2014)
Produced biennially, The World's Water is the most comprehensive and up-to-to date source of information and analysis on freshwater resources. Each new volume examines critical global trends and offers the best data available on a variety of topics related to water. Volume 8 features chapters on hydraulic fracturing (fracking), water footprints, sustainable water jobs, and desalination financing, among other timely issues. Water briefs provide concise updates on topics including the Dead-Sea and the role of water in the Syrian conflict. The World's Water is coauthored by MacArthur "genius" Peter H. Gleick and his colleagues at the world-renowned Pacific Institute. Since the first volume was published in 1998, the series has become an indispensable resource for professionals in government agencies and nongovernmental organizations, researchers, students, and anyone concerned with water and its use.
Foreword -- Introduction -- 1. Global Water Governance in the Twenty-First Century -- 2. Shared Risks and Interests: The Case for Private Sector Engagement in Water Policy and Management -- 3. Sustainable Water Jobs -- 4. Hydraulic Fracturing and Water Resources: What Do We Know and Need to Know? -- 5. Water Footprint -- 6. Key Issues for Seawater Desalination in California: Cost and Financing -- 7. Zombie Water Projects -- Water Brief 1. The Syrian Conflict and the Role of Water -- Water Brief 2. The Red Sea–Dead Sea Project Update -- Water Brief 3. Water and Conflict: Events, Trends, and Analysis (2011–2012) -- Water Brief 4. Water Conflict Chronology -- Data Section -- Water Units, Data Conversions, and Constants -- Comprehensive Table of Contents -- Comprehensive Index.
Keywords: Marine sciences; Freshwater; Sustainable development; Climate change; Environmental management; Marine & Freshwater Sciences; Sustainable Development; Climate Change; Water Policy/Water Governance/Water Management